Strategic role of leadership in strategy implementation in Zimbabwe's state owned enterprises - Mapetere, Denver; Mavhiki, Severino; Nyamwanza, Tonderai; Sikomwe, Shingirai; Mhonde, Christopher (Centre for Promoting Ideas, 2016)
The study aimed to explore the link between active leadership involvement and strategy implementation success in State Owned Enterprises in Zimbabwe. The study was conducted between July and October 2010 with a total of 188 respondents randomly selected from four State Owned Enterprises. The data was gathered through an interview and a self-administered open ended questionnaire. The study revealed a relatively low leadership involvement in strategy implementation leading to partial strategy success. Leadership has been failing to role model the ideal behaviour necessary for successful strategy implementation. The absence of a well crafted strategic vision and the lack of communication were also identified. The study concluded that leadership should be able to craft a vision for any strategic programme, design effective communication strategies as well as to role model behaviour changes that are consistent with new strategies.